Efektivitas Penerapan Integrated Clinical Pathway (ICP Terkait Manajemen Risiko Terhadap Kualitas Pelayanan Di Rumah Sakit : A Literature Review - -, Hadira; Syahrul, Syahrul; Rachmawaty, Rini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective : Clinical pathway is a process that involves multidisciplinary health professionals focusing on patient care in accordance with procedures on an ongoing basis, and with the application of clinical pathways in hospitals will have a plan in treating patients so that services are expected to be more effective, quality, quality maintained with controlled costs. Clinical Pathway as a risk evaluation mechanism evaluation tool to detect active and latent errors (latent / system errors) and near misses in Clinical Risk Management in order to maintain and improve patient safety. The purpose of writing this systematic review is to see the effectiveness of the application of clinical pathways related to risk management to service quality.Method: The search was carried out using a data base in writing a systematic review namely; Pubmed, Proquest, Willey and secondary searching, journals restricted to the last 15 years and other publications related to the topic of writing. The journals obtained used surveys and statistical descriptions to see the effectiveness of the application of clinical pathways to the quality of services in hospitals.Results: Overall the results of several research surveys of the 7 articles reviewed showed a significant positive correlation between the application of clinical pathways and the reduction in clinical risk of patient care in hospitals. There has been a stratification of the reduction in the number of days of hospitalization of patients and the index of hospitalization costs of patients in the hospital on the application of clinical flow so that it explicitly prevents over procedures such as the number of laboratory tests, number of consultations and medicines.Conclusion: The development of clinical pathway is proven to be able to improve multidisciplinary intra and inter communication, good teamwork and efficient maintenance planning. It also will automatically improve patient output, improve patient safety and provide patient satisfaction regarding service quality. To maintain optimal results and prevent the possibility of the impact of risks in clinical procedures, it is necessary to have intense, ongoing monitoring and commitment from the hospital and health workers in the implementation of clinical pathways in hospitals.